Intracellular Renin Disrupts Chemical Communication between Heart Cells. Pathophysiological Implications - De Mello, Walmor C. (Frontiers in Endocrinology, 2015)
Highlights Intracellular renin disrupts chemical communication in the heart Angiotensinogen enhances the effect of renin Intracellular enalaprilat reduces significantly the effect of renin Intracellular renin increases the inward calcium current Harmful versus beneficial effect during myocardial infarction The influence of intracellular renin on the process of chemical communication between cardiac cells was investigated in cell pairs isolated from the left ventricle of adult Wistar Kyoto rats. The enzyme together with Lucifer yellow CH was dialyzed into one cell of the pair using the whole cell clamp technique. The diffusion of the dye in the dialyzed and in non-dialyzed cell was followed by measuring the intensity of fluorescence in both cells as a function of time. The results indicated that; (1) under normal conditions, Lucifer Yellow flows from cell to cell through gap junctions; (2) the intracellular dialysis of renin (100 nM) disrupts chemical communication – an effect enhanced by simultaneous administration of angiotensinogen (100 nM); (3) enalaprilat (10−9 M) administered to the cytosol together with renin reduced drastically the uncoupling action of the enzyme; (4) aliskiren (10−8 M) inhibited the effect of renin on chemical communication; (5) the possible role of intracellular renin independently of angiotensin II (Ang II) was evaluated including the increase of the inward calcium current elicited by the enzyme and the possible role of oxidative stress on the disruption of cell communication; (6) the possible harmful versus the beneficial effect of intracellular renin during myocardial infarction was discussed; (7) the present results indicate that intracellular renin due to internalization or in situ synthesis causes a severe impairment of chemical communication in the heart resulting in derangement of metabolic cooperation with serious consequences for heart function.